ANALISIS MISKONSEPSI SISWA MTs MELALUI PEMBELAJARAN INKUIRI PADA MATERI SEGITIGA MENGGUNAKAN CERTAINTY OF RESPONSE INDEX (CRI) - Abdur Rohim (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2023)
This research is motivated by the many misconceptions (misconceptions) experienced by class VII students in the triangle material and the absence of previous research that examines misconceptions at MTs Hidayatus Salam. The purpose of this study is to describe the misconceptions experienced by MTs students through inquiry learning on triangle material and the factors that cause misconceptions. This type of research is a qualitative descriptive research conducted at MTs Hidayatus Salam Lowayu with using 6 subjects who experienced most misconceptions. Data collected with give test misconception completed triangle with table Certainty of Response Index (CRI) and semi- structured interview. Results Study show that: 1 ) there are differences in students' misconceptions, in the category of classificational type misconceptions in solving the triangle problem students meet the indicators of classificational misconceptions, namely, students To do error in classify between get up triangle. In the category of theoretical misconceptions, students meet the indicators of theoretical misconceptions, namely, students make mistakes in defining the concept of a triangle. In the category of correlational misconceptions, students meet the indicators of correlational misconceptions, namely students make mistakes in connecting the formulas used with the problems in the questions. 2) the causes of misconceptions are the lack of student learning experience, the teacher does not emphasize the concept, the lack of understanding the prerequisite concept, the inability of students to connect between concepts, students' initial conceptions are wrong and the context of everyday language.